Network Pharmacology and Bioinformatics Analysis Identifies Potential Therapeutic Targets of Paxlovid Against LUAD/COVID-19 - Zhang, Wentao; Yang, Zhe; Zhou, Fengge; Wei, Yanjun; Ma, Xiaoqing (Frontiers in Endocrinology, 2022)
Abstract Background: Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has caused a pandemic in many countries around the world. The virus is highly contagious and has a high fatality rate. Lung adenocarcinoma (LUAD) patients may have higher susceptibility and mortality to COVID-19. While Paxlovid is the first oral drug approved by the U.S. Food and Drug Administration (FDA) for the new crown, its specific drug mechanism for lung cancer patients infected with the new crown remains to be further studied. Methods: COVID-19 related genes were obtained from NCBI, GeneCards, and KEGG, and then the transcriptome data for LUAD was downloaded from TCGA. The drug targets of Paxlovid were revealed through BATMAN-TCM, DrugBank, SwissTargetPrediction, and TargetNet. The genes related to susceptibility to COVID-19 in LUAD patients were obtained through differential analysis. The interaction of LUAD/COVID-19 related genes was evaluated and displayed by STRING, and a COX risk regression model was established to screen and evaluate the correlation between genes and clinical characteristics. The Venn diagram was drawn to select the candidate targets of Paxlovdi against LUAD/COVID-19, and the functional analysis of the target genes was performed using KEGG and GO enrichment analysis. Finally, Cytoscape was used to screen and visualize the Hub Gene, and Autodock was used for molecular docking between the drug and the target. Result: Bioinformatics analysis of the clinical characteristics of LUAD combined with COVID-19, including: prognosis-related genes, survival rate, and clinical prediction model to screen out core genes. The key targets of Paxlovid against LUAD/COVID-19 were obtained through network pharmacology. Pathway analysis showed that during LUAD/COVID-19 treatment, Paxlovid regulated the IL-17 signaling pathway, Cytokine-cytokine receptor interaction. Conclusions: Based on bioinformatics and network pharmacology, the clinical characteristics of LUAD/COVID-19 patients were revealed. The potential therapeutic targets and molecular pathways of Paxlovid in the treatment of LUAD/COVID were identified.